2022
DOI: 10.3390/jcm11195956
|View full text |Cite
|
Sign up to set email alerts
|

Association between SGLT2 Inhibitors and Cardiac Rehabilitation Outcomes in Patients with Cardiovascular Disease and Type 2 Diabetes Mellitus

Abstract: The use of sodium-glucose cotransporter 2 (SGLT2) inhibitors in patients with type 2 diabetes mellitus (T2DM) has been associated with decreased skeletal muscle mass but remains unclear in patients with cardiovascular disease (CVD) undergoing comprehensive outpatient cardiac rehabilitation (CR). Therefore, this study investigates the effect of SGLT2 inhibitors on the outcomes of patients with CVD and T2DM undergoing comprehensive outpatient CR. The study included 402 patients with CVD and T2DM who participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Several studies have reported decreased skeletal muscle mass and weakness with SGLT2is in patients with type 2 diabetes mellitus [ 33 , 34 ]. However, another study reported that SGLT2is improved muscle strength, gait speed, and 6 min walk distance [ 35 ]. In patients with HF, SGLT2is have been shown to improve functional capacity, as assessed by peak VO2 [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported decreased skeletal muscle mass and weakness with SGLT2is in patients with type 2 diabetes mellitus [ 33 , 34 ]. However, another study reported that SGLT2is improved muscle strength, gait speed, and 6 min walk distance [ 35 ]. In patients with HF, SGLT2is have been shown to improve functional capacity, as assessed by peak VO2 [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%